Poligami dalam Perspekstif Epistimologi Falsifikasi: Polygamy from the Perspective of Falsification Epistemology - Fadri Sanafiah (Indonesia Berdaya, 2026)
This study examines the practice of polygamy from the perspective of falsification epistemology. The ideal of marriage is to establish a harmonious and lasting family; however, this ideal is often considered difficult or even impossible to achieve in polygamous marriages. Polygamy is frequently perceived as a source of family conflict, transforming what was once a happy household into one filled with tension and suffering. Some argue that this situation arises because Islam permits a husband to have more than one wife. This study critically examines such assumptions through a literature-based analysis. The research is expected to contribute both academically and practically. Academically, it enriches scholarly discourse and serves as a reference for future researchers by providing preliminary data and identifying issues that require further focused analysis. Practically, it provides information and insights for the wider community regarding the concept of polygamy in Islam. This research employs a qualitative descriptive-analytical approach using a library research method. The findings indicate that, within Islamic teachings, polygamy is permitted only as an exceptional measure to achieve the objectives of marriage under specific circumstances, such as when a wife is unable to bear children, suffers from a serious illness, or is no longer able to fulfill her marital responsibilities. Furthermore, polygamy is allowed only when it is genuinely necessary and under the strict condition that the husband is able to act justly toward all wives.   Abstrak. Penelitian ini mengulas tentang adanya poligami, ikatan perkawinan yang dicita-citakan tersebut sulit atau bahkan tidak akan tercapai. Sekejam itukah poligami? Kehidupan yang pada mulanya bahagia laksana surge, gara-gara poligami tiba-tiba berubah menjadi neraka. Ada nggapan, hal itu terjadi justru karena Islam telah mengabsahkan suami untuk beristri lebih dari seorang. Betulkah demikian?. Dari hasil penelitian ini diharapkan dapat member kegunaan secara akademis dan praktis, dari sisi akademis kegunaan penelitian di samping berguna bagi pengembangan ilmu penulis juga dapat bermanfaat bagi peneliti-peneliti yang akan datang. Pentingnya hasil penelitian ini bagi peneliti-peneliti yang akan datang terutama terletak pada sisi ketersediaan data awal, karakteristik termasuk masalah-masalah yang belum mendapatkan analisis yang fokus. Secara praktis penelitian ini berguna bagi informasi. Penelitian ini adalah penelitian pustaka (library research), bersifat kualitatif, deskriptif analitis. tujuan diperbolehkannya poligami dalam Islam adalah hanya sebagai pintu darurat untuk mewujudkan tujuan perkawinan, ketika seorang istri tidak mampu menghasilkan keturunan (mandul), atau ketika istri terjangkit penyakit parah atau sudah tidak mampu lagi melaksanakan kewajibannya sebagai seorang istri, Ia hanya dilalui saat amat diperlukan, dengan syarat yang berat, yaitu adil.